Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4314/tjpr.v12i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dissolution Test Method for Drotaverine Hydrochloride/Mefenamic Acid Combination Using Derivative Spectrophotometry

Abstract: Purpose: To develop and validate a dissolution test method for tablets containing 80 mg of drotaverine hydrochloride (DRT) and 250 mg of mefenamic acid (MEF DRT and MEF combination tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Other alternative which is also possible to be applied is by using surfactant which can increase the solubility of the drug significantly in physiological pH range, such as cetyl-trimethylammonium-bromide (CTAB) or cetrimide. Some studies have found that the addition of cetrimide could raise the solubility and dissolution rate of mefenamic acid to a far higher extent than those resulted by other surfactants, such as Tween 80 and SLS [ 12 , 13 ]. A study showed that the use of 1% CTAB in 900 mL of phosphate buffer at pH 6.8 could result in more than 80% mefenamic acid release from the 500-mg caplet after 30 min of dissolution time [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other alternative which is also possible to be applied is by using surfactant which can increase the solubility of the drug significantly in physiological pH range, such as cetyl-trimethylammonium-bromide (CTAB) or cetrimide. Some studies have found that the addition of cetrimide could raise the solubility and dissolution rate of mefenamic acid to a far higher extent than those resulted by other surfactants, such as Tween 80 and SLS [ 12 , 13 ]. A study showed that the use of 1% CTAB in 900 mL of phosphate buffer at pH 6.8 could result in more than 80% mefenamic acid release from the 500-mg caplet after 30 min of dissolution time [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…They belong to the class of non-steroidal anti-inflammatory drugs (NSAIDs), work by inhibiting the body’s production of prostaglandin, and are competitive inhibitors of cyclooxygenase (COX1 and COX2) [ 10 ]. Drotaverine Hydrochloride 1-(3, 4-diethoxybenzylidene)-6,7-methoxy-1,2,3,4-tetrahydroisoquinoline hydrochloride ( Figure 1 c) is an antispasmodic agent structurally related to papaverine [ 11 , 12 ], being a selective inhibitor of phosphodiesterase 4, with no anticholinergic effects. Recent studies on the action of this active substance on human cancer cell lines show that drotaverine can be used as a cytostatic agent, in addition to its normal use [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most commonly used active pharmaceutical ingredients with analgesic action is Ibuprofen (Ibu), while Drotaverine Hydrochloride (D-HCl) is employed for the antispasmodic effect. A binary system of active pharmaceutical substances with antispasmodic and analgesic action is Drotaverine Hydrochloride and Mefenamic acid mixture that is indicated for the symptomatic treatment of spasmodic dysmenorrhea, colic pains (including ureteric), biliary and intestinal colic [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…range of analytical techniques, viz UV spectrophotometry 9,10 , spectrofluorimetry 11,12 , HPLC [13][14][15] , HPTLC 16 , and electrochemistry 17 .…”
mentioning
confidence: 99%